Analysis of Factors That Influence Tax Avoidance in the Food and Beverage Industry - Indrati, Menik; Agustiningsih, Wulandari; Purwaningsih, Eny; Baskara, Ika (Jurnal Ilmiah Global Education, 2024)
This study aims to investigate the influence of internal factors on tax avoidance in the food and beverage industry in Indonesia. Variables such as the presence of a Board of Directors, Female Directors, company profitability, laverage and company size are analyzed for the company's tendency to avoid taxes. Data collection was carried out from the financial reports of food and beverage subsector companies listed on the Indonesia Stock Exchange during the 2019-2022 period. Multiple linear regression analysis is used to test the relationship between the independent variable and the dependent variable. The results show that the Board of Directors, profitability, and company size significantly influence tax avoidance in the food and beverage industry. The implications of these findings guide practitioners in designing effective tax strategies to optimize company performance.